(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute ischemic stroke is a leading cause of mortality and long-term disability worldwide. Recombinant tissue plasminogen activator (rtPA) remains the standard thrombolytic therapy when administered within the recommended therapeutic window. However, rural healthcare settings face significant barriers that may delay timely thrombolysis. This study aimed to evaluate the outcomes and barriers associated with rtPA therapy in acute ischemic stroke patients managed at a rural tertiary care center. Methodology: This prospective observational study was conducted in the Department of Emergency Medicine at Sree Mookambika Institute of Medical Sciences, Kulasekharam, from May 2025 to February 2026. Patients with CT-confirmed acute ischemic stroke eligible for intravenous rtPA were included. Baseline demographic, clinical, imaging, and socioeconomic data were recorded. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS). Outcomes were evaluated using NIHSS at discharge and modified Rankin Scale (mRS) at one and three months follow-up. Treatment delays including door-to-imaging and door-to-needle times were analyzed. Statistical analysis was performed using SPSS version 25.0. Result: Among 28 patients treated with rtPA, no major bleeding complications were observed. Meaningful functional improvement at three months follow-up was seen in 35.7% of patients. Mean door-to-imaging time was 21 minutes, while mean door-to-needle time was 68 minutes. Delays were mainly related to socioeconomic factors, delayed decision-making, and limited awareness regarding stroke symptoms and thrombolytic therapy. Conclusion: Thrombolysis with rtPA is safe and feasible in rural tertiary care settings. Improving public awareness, reducing treatment delays, and strengthening rural stroke care systems may further improve outcomes in acute ischemic stroke patients.